2015
DOI: 10.1021/acschemneuro.5b00033
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms of Serotonin Signaling

Abstract: Histone modifications and DNA methylation represent central dynamic and reversible processes that regulate gene expression and contribute to cellular phenotypes. These epigenetic marks have been shown to play fundamental roles in a diverse set of signaling and behavioral outcomes. Serotonin is a monoamine that regulates numerous physiological responses including those in the central nervous system. The cardinal signal transduction mechanisms via serotonin and its receptors are well established, but fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 133 publications
0
24
0
1
Order By: Relevance
“…However, considering the number of serotonergic receptors and their variations, it is beyond the scope of this paper to review all of them here. For a review of 5-HT receptor-dependent signaling and environmental impact on brain development see: Holloway and Gonzalez-Maeso (2015).…”
Section: Influence Of Genetic and Epigenetic Factorsmentioning
confidence: 99%
“…However, considering the number of serotonergic receptors and their variations, it is beyond the scope of this paper to review all of them here. For a review of 5-HT receptor-dependent signaling and environmental impact on brain development see: Holloway and Gonzalez-Maeso (2015).…”
Section: Influence Of Genetic and Epigenetic Factorsmentioning
confidence: 99%
“…This leads to deregulation of histone deacetylase 2 (HDAC2), and subsequent epigenetic variations of glutamate metabotropic receptor 2 gene ( GRM2 ). This may affects response to treatment with GRM2 inhibitors (Holloway & Gonzalez‐Maeso, ).…”
Section: Serotonin Pathway Genes Associated With Szmentioning
confidence: 99%
“…Gene annotation revealed that LOC103692976 is involved in the positive regulation of cyclin-dependent protein serine/threonine kinase. DNA methylation plays a role in the control of neurotransmission [58]. The LOC100910540 gene, which is related to methylation, was up and down-regulated in the E vs M and E + L vs E comparisons, respectively.…”
Section: Discussionmentioning
confidence: 99%